Hasisadra's Adventure : Essay #7 from "Science and Hebrew Tradition" - Huxley, Thomas Henry, 1825-1895 (Salt Lake City, UT : Project Gutenberg, 2001)
"Hasisadra's Adventure" by Thomas Henry Huxley is an essay that delves into the ancient Mesopotamian narrative of a great flood, woven through myth and history. Written in the late 19th century, it explores the story of Hasisadra, a figure who, forewarned of an impending deluge, builds a ship to save himself, his family, and various animals. Huxley's work is part of a broader discourse on the intersection of scientific inquiry and religious texts, particularly focusing on the legitimacy of ancient flood stories within the framework of modern science. The narrative begins in the city of Surippak, where Hasisadra receives a dream warning him of an impending flood. He constructs a ship and embarks on a voyage of survival as a cataclysm engulfs the land. After the flood subsides, he sends out various birds to seek land, ultimately grounding his vessel on the mountains of Nizir. Huxley contextualizes this tale within the ancient civilizations of Mesopotamia, linking it to the broader themes of myth-making, divine intervention, and human survival. He critically examines the historical veracity of such accounts while engaging with scientific interpretations of potential flood events in the Euphrates Valley, ultimately questioning the reliability of both the narrative and the myths surrounding divinity in the context of empirical evidence. (This is an automatically generated summary.)
Release date is 2001-05-01
Produced by D. R. Thompson, and David Widger
Keywords: Science; Evolution; Bible and science; Paleontology